Where would you open a new Pizza Restaurant in Buenos Aires? - Maraggi, Santiago (2020)
The goal of the work is to extract an initial guideline to determine the best place to open a new Pizza Restaurant in Buenos Aires. In this work the K-Means algorithm was applied to classify the neighborhoods of Buenos Aires, according with their most common venue types. For each neighborhood, top 50 most common venue types were established, and then, 10 neighborhood clusters were obtained with the mentioned algorithm in order to provide some clues about which neighborhoods could be best investment options.